Excel guide to finite mathematics and applied calculus - Narasimhan, Revathi (Thomson/Schirmer, 2007)
This market-leading book for the Fundamentals of Music course addresses students' differing abilities. Internationally renowned composer William Duckworth covers the fundamentals in 14 concise main chapters that are supplemented by 11 enrichment appendices. These offer extended coverage for teachers or students who desire additional instruction. With a practical focus on developing skills, Duckworth presents many clear examples that show students the basics. Because students can best learn the fundamentals by using them, written and aural exercises give students the opportunity to creatively apply their knowledge in realistic music situations